Electric truck market analysis - An analysis on the implementation and development of the electric truck market for transportation in Europe 2023 - Berntsson, Fabian; Petkovski, Viktor (My University, 2023)
In today's global society, the need for transportation has increased both internationally and within Sweden. The transportation sector generates significant amounts of greenhouse gases, and in Sweden, it alone accounts for about a third of the country's total carbon dioxide emissions. It is therefore of utmost importance to find new, climate-smart solutions for transportation. Electric trucks are becoming an increasingly common means of transport, primarily within shorter transport distances. Key factors influencing the development and adoption of electric trucks within the logistics industry will be examined. The focus is on issues such as charging time, safety, and range, which are major obstacles to expanded use, infrastructure, and battery technology. The research is based on literature searches and interviews with leading companies within the industry and analyzes the challenges that the development and spread of electric trucks on the market face. The report's limitations are also discussed, which include the exclusion of any calculations and focus solely on electric trucks within the logistics industry in Europe. The significance of the findings is highlighted, as advancements in battery technology, charging infrastructure, and regulations drive the adoption of electric trucks, which is expected to continue in the coming years. The study emphasizes the importance of electric trucks in achieving sustainable transportation solutions and describes the companies' commitment to investing in research and development to achieve this goal.
Keywords: Electric trucks; the logistics industry; charging time; safety; range; sustainability; Volvo Trucks; Scania; battery technology; charging infrastructure